Metabolic Tumor Imaging with Rapidly Signal‐Enhanced 1‐13C‐Pyruvate‐d3. Issue 2 (26th October 2022) - Hune, Theresa; Mamone, Salvatore; Schroeder, Henning; Jagtap, Anil P.; Sternkopf, Sonja; Stevanato, Gabriele; Korchak, Sergey; Fokken, Claudia; Müller, Christoph A.; Schmidt, Andreas B.; Becker, Dorothea; Glöggler, Stefan
Abstract: The metabolism of malignant cells differs significantly from that of healthy cells and thus, it is possible to perform metabolic imaging to reveal not only the exact location of a tumor, but also intratumoral areas of high metabolic activity. Herein, we demonstrate the feasibility of metabolic tumor imaging using signal‐enhanced 1‐ 13 C‐pyruvate‐d3, which is rapidly enhanced via para‐hydrogen, and thus, the signal is amplified by several orders of magnitudes in less than a minute. Using as a model, human melanoma xenografts injected with signal‐enhanced 1‐ 13 C‐pyruvate‐d3, we show that the conversion of pyruvate into lactate can be monitored along with its kinetics, which could pave the way for rapidly detecting and monitoring changes in tumor metabolism. Abstract : The feasibility to image cancer with MRI by rapidly enhanced 1‐ 13 C pyruvate‐d3 using para‐hydrogen is introduced.